Pengaruh Media Video Animasi Melalui Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Siswa - Anisa Uroiva; Agustiningsih; Kendid Mahmudi (Cetta: Jurnal Ilmu Pendidikan, 2022)
The application of video media in learning that is less than optimal is due to one of the reasons for the limited facilities. Learning media as a means of distributing information to students cannot be obtained by students optimally. This study describes the impact produced by animated video learning media on students' cognitive learning outcomes. The aim is to determine the effect on student cognitive learning outcomes caused by animated video media whose use is supported by a guided inquiry learning model. The type of research is experimental with the design that is used as a reference is the non-equivalent control group design. The subjects used were students of SDN 1 Pesanggaran with class VA and class VB being the observed sample. The experimental activity carried out was the prvision of treatment in the form of learning that utilized animated video media with a guided inquiry learning model as a learning style. After the research was conducted, the results of the students’ initial and final tests (pre and post) were obtained. Each result of the initial ability test of students from the two classes is the control class = 61,84 while the experimental class = 58,01. After the experimental class was treated and the control class was not, the posttest result were obtained, namely the control class was 75,61 while the experimental class was 82,05. Based on the t-test, it is known that the value of tcount=4,545 and the price of ttabel=1,665. Referring to the calculation of the t-test, namely tcount > ttable, the result of the decision is the use of animated video media wich is supported by a guided inquiriy learning model that has an impact on students’ cognitive learning outcomes. there is an effect of using animated video media through guided inquiry learning models on students’ cognitive learning outcomes. Then the calculation of the relative effectiveness value shoews that the application of animated video media through the guided inquiry learning model is relatively effective at 57%.